Constitutive framework of a new hyperelastic model for isotropic rubber-like materials for finite element implementation - Stumpf, Felipe Tempel (2021)
The strain energy function of hyperelastic material models must fulfill some mathematical conditions to satisfy requirements such as numerical stability and physically plausible mechanical behavior. In the framework of computer simulations with Newton-type methods, numerical stability is assured by the positive definiteness of the tangent operator. The Baker-Ericksen inequalities, on the other hand, are sufficient and necessary conditions in order to guarantee that the material behaves in a physically plausible way, although they are rarely taken into account during parameter identification. The present work proposes a modification in the strain energy function of a previously developed model for isotropic rubber-like materials. The new expression for W allows the satisfaction of both of the aforementioned requirements. The complete constitutive framework for its implementation in a Finite Element code is provided. Representative examples are analyzed and to show the superior performance when compared to well-known models found in the specialized literature both for homogeneous and non-homogeneous cases of deformation.